Phase Measurement Of Acoustic Wave Propagation In Double Channel Video Based Interferometry - Munajat, Yusof; Suaidi, Mohamad Kadim (Penerbit UTM Press, 2001)
Phase measurement interferometer system was developed by modifying the phase difference between two outputs of Mach-Zehnder interferometer by approximately 90Â° out of phase. System is developed in order to overcome some ambiguity of fringe shift in studying acoustic wave propagation and associate transient pressure profile. Two set of images were captured from two outputs of Mach-Zehnder interferometer in the event of with and without acoustic wave disturbance. The phase change over the interferograms were mapped and analysed separately and simultaneously. Simultaneous phase mapping gives better result and overcome ambiguity problem.